KELAYAKAN PROGRAM HUTAN DESA DI DESA TANJUNG AUR II KECAMATAN PINO RAYA KABUPATEN BENGKULU SELATAN - Desmantoro Desmantoro; Nurheni Wijayanto; Leti Sundawati (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2016)
A feasibility study toward the prerequisite conditions is required for the successful implementation of  the Village Forest program in Tanjung Aur II Village. This study aims to: 1) identify bio-geophysical conditions of  the work area; 2) analyze the conditions of  sosioeconomic-cultural society/institutional; 3) analyze the support of  stakeholders; and 4) formulate appropriate implementation strategies. The study was using survey method and qualitative studies with multiple analysis techniques. The results showed that: 1) the biogeophysical conditions was eligible and suitable to be proposed as village forest working area; 2) conditions of  socio-economic-cultural communities enable to form village forest management institution, through collaboration between state forest encroachers and the villager representatives; 3) stakeholders were ready to provide support facilitation and assistance according to their capacity and capabilities. Key stakeholder were among others BPDAS Ketahun, Dishut Provinsi Bengkulu, Dishut ESDM Bengkulu Selatan, NGOs Ulayat, andofficials of  the Village; 4) the implementation strategy of  village forest program that suitable for Tanjung Aur II was a competitive strategy or diversification (S-T strategy), with the main priority of  the strategy, among others by seeking and asking for support from relevant stakeholders or other parties who had capacity and capability to undertake facilitation and assistance.